Local Coffee Shop Use of Sensory Marketing to Maintain Customer Loyalty: The Mediating Role of Customer Satisfaction - DWIPUTRI, ALODIA LASTRI (AIBPM Publisher, 2024)
Indonesia boasts the world's fourth-highest coffee consumption, with demand steadily rising. Interestingly, nearly 25% of coffee drinkers are social drinkers, which means they enjoy coffee primarily when catching up with friends at cafes. However, the coffee shop market is saturated, leading to fierce competition among coffee shops struggling to retain customers. Loyalty is scarce, with most customers flitting between cafes. We explore whether customer satisfaction mediates the relationship between sensory marketing and loyalty. Existing research suggests a link between sensory marketing, customer satisfaction, and ultimately, customer loyalty. This study aims to analyze and test this connection within the Indonesian coffee shop landscape. This research focuses on loyal customers of the chosen cafes, targeting those who have visited more than once. The method used in this study is quantitative with the technique of distributing questionnaires, then the results will be calculated using SMART PLS ver. 3.9 accompanied by descriptive analysis for explanation.